Kemampuan Pemecahan Masalah Kontekstual Siswa SMA pada Materi Barisan dan Deret - Meylia Dwi Jayanti; Edy Bambang Irawan; Santi Irawati (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: This article was a study that aims to describe the contextual problem solving skills of senior high school students. We used problem solving indicator based on Polya. The results of this study indicated that on stage of understanding the problem, 8% of all students could understand every word of the problem but some students were wrong in writing what was known and asked from the problem. At the stage of planning the strategies of solving problems, 43% of all students could construct the solving plan for the question given. At the stage of implementing a plan, 33% of all students could finish all steps chosen to solve the problems systematically. In the last stage, i.e: checking the answers obtained, 16% of all students were able to check the answers back but some students were not able enough to check back the answers obtained. Abstrak: Artikel ini merupakan suatu kajian yang bertujuan untuk mendeskripsikan kemampuan pemecahan masalah kontekstual siswa SMA. Analisis data dalam kajian ini menggunakan indikator kemampuan pemecahan masalah Polya. Hasil kajian menunjukkan pada tahap memahami masalah sebesar 8% siswa dapat memahami setiap kata pada soal tetapi beberapa siswa salah dalam menuliskan apa yang diketahui dan ditanyakan dari soal. Pada tahap menyusun rencana penyelesaian sebesar 43% siswa dapat menyusun rencana penyelesaian dari soal tersebut. Pada tahap melaksanakan rencana sebesar 33% siswa mampu menyelesaikan semua langkah yang telah disusun untuk menyelesaikan soal tersebut dengan runtut dan sitematis. Pada tahap terakhir memeriksa kembali hasil jawaban sebesar 16% siswa mampu melakukan pengecekan jawaban, tetapi beberapa siswa kurang mampu dalam mengecek kembali jawaban yang didapatkannya.